Graphic memoirs and trans life writing: the transmasculine self representation in Lino Arruda’s Monstrans - Passos, Mateus Yuri; Trombini, Miguel (Dialogos, 2024)
This article is dedicated to discussing how the possibility of producing one’s own stories and narrating one’s experiences enables the perception of the plurality of experiences of transgender persons. Focusing on the graphic memoir scene, we evaluate the maturity of this medium to, in sequence, present a brief analysis of Monstrans: experiencing horrormones, autobiographical graphic novel by Brazilian comic artist Lino Arruda, addressing both the different ways in which the author visually constructs his self-representation and the way he cuts and structures moments of his life.